Peer-Mentoring Processes: Commentary on the Stop the Violence Train the Trainers Program - Adusei, Kwadwo (Advances in Social Sciences Research Journal, 2018)
Recent episodes of violence among African youth in Australia have been a concern for the Police and the African communities in the country. In Western Australia, the Police and the African communities in Perth have been searching for ways to reduce and prevent recent spates of violence among African youth in Perth. This paper presents preliminary findings of the impact of a pilot a youth mentoring program to create awareness among African youth in Western Australia about crime prevention. Dubbed “Stop the Violence Program”, the initiative advocated the use of trained and resourced local champions to mentor their peers on preventing anti-social behaviours. The program was collaboration between the Edith Cowan University, the Western Australia’s Organisation of African Communities and the Office of Multicultural Interests.